(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Nursing care is an essential and integral part of palliative care, as it provides emotional support, pain management, and comprehensive care approaches to patients and families with life-limiting illnesses. However, little is known about the satisfaction, perceptions, and expectations of nursing care among nurses, patients, and families in palliative care settings. This paper aims to address this gap by adopting a mixed methods design that combines qualitative and quantitative approaches to collect and analyze data from a large and diverse sample of nurses, patients, and families in palliative care settings. The paper finds that nursing care in palliative care settings is generally satisfactory and appreciated by patients and families, but also reveals some areas of concern and improvement. The paper also finds that nursing care in palliative care settings is perceived and expected to be comprehensive and holistic, but also faces some challenges and barriers. The paper also finds that nursing care in palliative care settings is influenced by various factors, such as the role and scope of nursing, the availability and accessibility of resources and support, and the expectations and preferences of patients and families. The paper contributes to the advancement and transformation of palliative care through nursing practice, education, and policy. The paper also provides recommendations and suggestions for enhancing the skills and competencies of nurses, incorporating palliative care content and pedagogy into the nursing curriculum, and promoting and improving the access and integration of palliative care for patients and families.